Coerência e coesão na interpretação de textos em provas de concursos públicos - Martino, Agnaldo Sérgio de (2008)
This essay, oriented to a Text and Speech in Oral and Written Manners approach, studies how the principles of cohesion and coherency may be applied to analysis of text comprehension questions from public concourse examinations, with the purpose of achieving an objective response towards the analyzed question. Cohesion and coherency were already largely discussed by a number of authors, and to each discussion new observation and classification proposals were proposed, related to the principles of cohesion and coherency as well. The essay revises some studies which were written regarding these issues and uses them as base for the development of possible purports for the texts. Having as objective reach to an answer solely to the question proposed in the examination of a public concourse, the several textual marks left by the text producer are observed as to the reader redeems and uses them as support to an objective interpretation of the text